Subsurface Instability Characterization Using the Microtremor HVSR Method for Landslide Risk Assessment in Sriharjo Village, Bantul, Yogyakarta, Indonesia - Udi Harmoko; Gatot Yuliyanto; Irham Nurwidyanto; Sugeng Widada (Jurnal Penelitian Pendidikan IPA, 2025)
Sriharjo Village, Bantul, Yogyakarta, is affected by recurrent mass movements and slope deformations due to complex geological conditions and groundwater infiltration. This study aims to assess subsurface instability using the Horizontal-to-Vertical Spectral Ratio (HVSR) method. Fifty-three microtremor measurements were conducted along four survey lines, with each recording lasting approximately 20 minutes. The data were processed using Geopsy and Dinver software, employing spectral curve analysis to extract key subsurface parameters. The analysis yielded shear wave velocity (Vs), compressional wave velocity (Vp), Vp/Vs ratio, and Poisson’s ratio. Vs values below 750 m/s indicate soft, less consolidated materials, typically associated with unconsolidated sediments. High Vp/Vs ratios (>2.5) and Poisson’s ratios approaching 0.5 suggest elevated pore water content and low shear strength, indicating saturated and nearly incompressible conditions. Spatial patterns reveal subsurface fluid migration from the north toward the deformation zone, highlighting the role of groundwater infiltration and increased pore pressure in triggering slope instability. This study demonstrates that the interaction between pore pressure and lithological heterogeneity contributes significantly to the development of slip surfaces and ongoing deformation. The findings provide a geophysical framework applicable to slope stability assessment and landslide risk mitigation in vulnerable terrains such as Sriharjo Village.